Online Propaganda and Disinformation in Russian Ukrainian conflict - Maria ENACHI (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
This paper examines propaganda and disinformation in the context of the Russian-Ukrainian conflict, paying particular attention to the role that social media and the internet played between March 2022 and March 2023. Both sides in the conflict used the online environment to shape public perceptions: Russia, through an intense disinformation campaign, and Ukraine, by attracting international support. Social media platforms have implemented measures to counter Russian disinformation, raising questions about information control and potential consequences for freedom of expression. Disinformation has had a significant impact on public trust in different types of media, with a trend of increasing trust in traditional (audiovisual) sources and decreasing trust in digital platforms. Russian tactics such as the use of "troll factories" and fake social media accounts have been key elements in this campaign. The importance of this topic is that it illustrates the critical dimension of information warfare in modern conflicts, where the manipulation of public perceptions can influence not only international support but also the legitimacy of the governments involved.